Analysis of the effect of camelina oil on the skin after a single use - Gogosz, Anna; Szlachetka, Agata; Kurkiewicz-Piotrowska, Anna (Health Promotion & Physical Activity, 2025)
The aim of this study was to evaluate the effect of a single application of Camelina sativa oil (also known as false flax oil) on selected skin properties of the medial forearm, including skin hydration, transepidermal water loss (TEWL), and elasticity. The study involved 20 healthy women aged 22–26 years. Skin parameters were assessed four times: at baseline, after inducing a model disruption of the skin barrier using the tape stripping method, and then 1 hour after application of the tested oil on both disrupted and intact skin. Specialized, scientifically certified devices were used, including a corneometer, tewameter, cutometer, and indentometer. A significant increase in skin hydration was observed following oil application, both on disrupted and intact skin. No effect of Camelina sativa oil on skin barrier function (TEWL) or on elasticity parameters measured with cutometry and indentometry was observed. The results confirm that camelina oil exhibits rapid moisturizing effects. No reduction in TEWL was observed, suggesting that the tested oil behaves similarly to drying oils. The lack of effect on other biomechanical skin properties after a single application does not rule out potential effects during prolonged use, which would require empirical confirmation in further studies.